Strategi Madrasah Ibtidaiyah Dalam Mengembangkan Kurikulum Yang Adaptif Terhadap Kebutuhan Peserta Didik di MI Grobagan Surakarta : Penelitian - Arum Puspa Dewi; Aqila Fadia Hayya Anwar; Annisa Nur Khoiriyyah; Khosyi’ah Qurrota A’yun; Praptiningsih (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to identify the strategies implemented by Madrasah Ibtidaiyah in developing an adaptive curriculum that meets students’ diverse needs at MI Grobagan Surakarta. This research employed a qualitative approach using observation, interviews, and documentation as data collection techniques. The results reveal that adaptive curriculum development is designed to align learning activities with students’ characteristics and learning needs. The implementation of the Merdeka Curriculum provides flexibility for teachers through phased learning structures that allow adjustments in learning outcomes. Additionally, the madrasah develops local Islamic content such as Hadith Arbain and Tahfidz to strengthen students’ religious character. The curriculum development process is participatory and collaborative, involving the principal, teachers, foundation, and school committee. Institutional support includes the provision of technology-based learning facilities and periodic evaluation of teacher performance. Overall, the implementation of the adaptive curriculum has a positive impact on students’ motivation and learning engagement, encouraging more active, contextual, and student-centered learning.